SOURCES OF DEVELOPMENT OF POETIC GIFT NIKOLA GUMILOV - Т.V. Huzynina (Academy of Cognitive and Natural Sciences, 2004)
The article deals with the sources, peculiarities and motivation of poetry o f Nikolai Gumilyev.